2022
DOI: 10.5194/bg-19-4801-2022
|View full text |Cite
|
Sign up to set email alerts
|

Seed traits and phylogeny explain plants' geographic distribution

Abstract: Abstract. Understanding the mechanisms that shape the geographic distribution of plant species is a central theme of biogeography. Although seed mass, seed dispersal mode and phylogeny have long been suspected to affect species distribution, the link between the sources of variation in these attributes and their effects on the distribution of seed plants are poorly documented. This study aims to quantify the joint effects of key seed traits and phylogeny on species distribution. We collected the seed mass and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…It has been well documented that the latitudinal gradient explain much of the global variation (> 51%) in seed mass (Moles et al, 2007), but this is the first report of the magnitude of seed mass variation within different dormancy types. Previous studies have also reasoned that global variation in seed mass might be an important driver of species distribution with more than 46% of variation in species distribution accounted for seed mass, seed mass variability and seed dispersal mode (Moles et al, 2007; Chen et al, 2022). Variation in seed mass can explain geographical ranges within which plants can thrive, leading to the different ecological strategies that have evolved in plants (Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well documented that the latitudinal gradient explain much of the global variation (> 51%) in seed mass (Moles et al, 2007), but this is the first report of the magnitude of seed mass variation within different dormancy types. Previous studies have also reasoned that global variation in seed mass might be an important driver of species distribution with more than 46% of variation in species distribution accounted for seed mass, seed mass variability and seed dispersal mode (Moles et al, 2007; Chen et al, 2022). Variation in seed mass can explain geographical ranges within which plants can thrive, leading to the different ecological strategies that have evolved in plants (Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reasoned that global variation in seed mass might be an important driver of species distribution with more than 46% of variation in species distribution accounted for seed mass, seed mass variability and seed dispersal mode (Moles et al, 2007; Chen et al, 2022). Variation in seed mass can explain geographical ranges within which plants can thrive, leading to the different ecological strategies that have evolved in plants (Chen et al, 2022). Moreover, empirical studies have reported that there is a trade-off between seed mass and seed dormancy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive organs could come from another part of the terrestrial forest close to the shoreline; then, they reach the delta area to grow as vegetation establishments (Chen et al 2020;Correa et al 2022;Wendt et al 2022). The tidal mechanism affects the distribution of reproductive organs predominantly to the inland area since the high tide in the nature reserve and owing to the flat area leading to the rising water river surface.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nonparametric analysis of variance (nonparametric ANOVA) with the Kruskal–Wallis test was used to assess dormancy percentage differences among species using the “kruskal.test” function in the stats package in R. As closely related species tend to have similar SDS (Felsenstein, 1985 ), Blomberg's K was calculated as an index of phylogenetic conservatism. Any K value significantly higher than zero can be regarded as trait evolution approaching Brownian motion to varying degrees (Chen et al, 2022 ). This metric was calculated using the “phylosig” function in the R package phytools with arcsine‐transformed mean dormancy percentages of all populations for each species (Baskin & Baskin, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…As closely related species typically experience similar natural selection pressures and seed traits can be constrained by phylogenetic history, species with a common ancestor often exhibit similar SDS (Chen et al, 2022 ; Seglias et al, 2018 ). For example, morphological dormancy is considered the ancestral state of seed dormancy and is observed in primitive taxa such as Taxaceae, Ginkgoaceae, and Podocarpaceae (Finch‐Savage & Leubner‐Metzger, 2006 ).…”
Section: Introductionmentioning
confidence: 99%